Evaluasi Aspek Usable, Valueable, dan Useful pada Aplikasi Pembelajaran Pemrograman Grasshoper menggunakan Parameter UX Honeycomb - Abdurahman Abdurahman; Satrio Hadi Wijoyo; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
In this digital era a lot of people looking for a knowledge and study through internet networks, one of the example is e-learning. E-learning not only used by college student but now a lot of school also use e-learning to teach their stundents. Grasshopper application is one the elearning that used to study javascript programming language. But grsshopper also has its own weakness acording to users complain. That is why the grasshopper aplication will be evaluated. The purpose of this evaluation is to know how good is the user experience of the application and also for consideration in the future uodate of the application. UX Honeycomb indicator is used as a basis to measure the level of user experience. In this study the respondents are divided into two categories that is <19 years and 19-24 years. Respondents in each category contained 30 people and the total respondents there are 60 people. Questionnaire is used as the metode in this study. The data from the questionnaire will beprocessed using statistic descriptive metode. The result of the processed data shows that the usable aspect in in good category because it has an average of 66.75%. the valuable aspect is in the good category because it has an average of 68.37%. and the useful aspect also in the good category because it has an average of 74.6%.